Greek CPR BLS Certified Providers have Confidence in Covid19 Vaccination. A Cohort Analysis in the Pre-Mandatory Vaccination Period by the Hellenic Society of Cardiology - Latsios, George; Leopoulou, Marianna; Synetos, Andreas; Stamatopoulou, Evangelia; Parisis, Charalambos; Karanasos, Antonios; Papanikolaou, Aggelos; Βounas, Pavlos; Toutouzas, Konstantinos; Kanakakis, John; Tsioufis, Kostas (Cardiology and Cardiovascular Medicine, 2022)
Objective: To evaluate the attitude towards vaccination (in general and especially towards Covid19) in a sizeable cohort of Greek Basic Life Support (BLS) certified providers. Methods: Certified providers from courses held by the Hellenic Society of Cardiology mainly in Athens, Greece (5.513 BLS participants) were asked to complete an electronic survey during June 2021. The study took place during the early stages of worldwide Covid19 vaccination and, more importantly, before any mandatory anti-Covid19 vaccination health policies were introduced. Notable that all providers attended the certified BLS seminars on a voluntary basis. Results: The vast majority had undergone vaccination against Covid19. Among those that had not been vaccinated, doubt towards vaccine’s effectiveness was reported as the main motive, followed by the fear of possible side-effects. The majority of the responders had vaccinated their children in accordance to the National Greek vaccination programming and more than half had also been vaccinated against common flu. Regarding the responders’ trust in the effectiveness of the Covid19 vaccine, it is correlated with previous Covid19 infection, a health-related profession, having a close family member or friend with a previous Covid19 infection, trust towards Covid19 vaccines and vaccines in general and the reliance that Covid19 vaccines can both help intercept the pandemic and promote public health. As their source of medical information, they trust their personal physician and other specialized scientists and much less the government officials or relatives and friends. Conclusion: Greek certified BLS providers report great confidence in the effectiveness of vaccination in general and especially against Covid19, irrespective of any